Production of reducing sugar in Solid State Fermentation (SSF) using aspergillus fumigatus / Musfirah Azmi - Azmi, Musfirah (Faculty of Applied Sciences, 2016)
Production tones of wastes of oil palm frond from oil palm industries affects the environment. This study is about conversion process from wastes of oil palm frond fiber into usable form of biosugar in the solid state fermentation (SSF) through enzymatic reaction using Aspergillus fumigatus. There were two parameters investigated; first was the particle size of oil palm frond fiber and second was moisture content fiber towards the production of reducing sugar. The two particles size of OPF in this study were 100μm and 250μm and fermentation process was carried out for 10 days. The maximum reducing sugar was at 70% moisture level for 250μm of OPF at 24.780μmole. Statistical analysis showed both particle size of oil palm frond fiber, 100μm and 250μm had no significant different towards production of reducing sugar in SSF by Aspergillus fumigatus. However, the effect of moisture content fiber do affect the production of reducing sugar in Solid State Fermentation of Oil Palm Frond by Aspergillus fumigatus. Water fed strategy used had increase the moisture content in feeding media and significantly produced high yield of reducing sugar in SSF. Analysis by using two-way ANOVA suggested that presence of water fed has significant different towards production of reducing sugar in SSF and resulted in higher production of reducing sugar.